Problems of Chronic Obstructive Pulmonary Disease (COPD) Among Workers - Agus Dwi Susanto (Jurnal Respirologi Indonesia, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a common, preventable and treatable disease that is characterized by persistent respiratory symptoms and airflow limitation that is due to airway and/or alveolar abnormalities usually caused by significant exposure to noxious particles or gases. Occupational exposure as a one of important risk factor that contribute for COPD on nonsmoker patients. Several studies at population consistent showed that COPD correlated with hazards exposure at work place. COPD among workers can decrease quality of life, increase of work impairment, work disability and hospitalitation also increase of abstinentia from work and decrease of work productivity. Prevention were major action to prevent incident and morbidity of COPD among workers. Prevention programs including primary, secondary and tertiary prevention.